Programy na rzecz równowagi życia zawodowego i rodzinnego - Dąbrowska, Karolina (Annales. Etyka w Życiu Gospodarczym, 2014)
The article is devoted to the problem of work-life balance. Nowadays more and more benefits is being perceived that stem from implementation of the industrial culture based on balance between work and life. On the other hand there are various limitations which in some cases hinder. One of such barriers lays in the process of communication. Moreover, the article discuss the process of gaining competitive advantage on the ground of the idea of work-family balance. The idea seems to be positive especially for the employees, organisation and even the whole society, since it can prevent the phenomenon of professional burnout. It also helps to maintain the most efficient and the best among the employees, who are intentionally aimed at achieving their goals in professional and personal life. The work- -family balance programmes can make a positive impact on the firm’s reputation and its perception by potential employees. The pregnant women and young parents are presented as a group most interested in those flexible solutions and the programmes prepared for them in LG Electronics, IBM, Decora SA, IKEA, BZ WBK, Volkswagen Motor Polska are examined.